Case of Insulinoma in a 2-Months-Old Infant - Pangestika, Niluh Putu Wida; Arimbawa, I Made; Yuda, I Made Darma; Suparyatha, Ida Bagus Gede; Wati, Dyah Kanya; Hartawan, I Nyoman Budi; Ariyanta, Kadek Deddy; Darmajaya, I Made; Kurniyanta, I Putu; Maker, Luh Putu Iin Indrayani; Anandasari, Pande Putu Yuli; Wande, I Nyoman (Open Access Macedonian Journal of Medical Sciences, 2022)
INTRODUCTION: Insulinoma is congenital hyperinsulinism of infancy (CHI). It is a type of functional neuroendocrine tumor (NET) in the pancreas that manifests with persistent hypoglycemia caused by inappropriately high secretion of insulin (hyperinsulinemia). Comprehensive and multidisciplinary management is required for a better outcome. CASE PRESENTATION: A 2-months-old girl came to the Emergency unit Sanglah Hospital, with a chief complaint of seizure. The patient had a low blood glucose level, high fasting insulin, high LDH, computed tomography of the abdomen result showed isodense heterogeneous lesions border in the cauda pancreas with size 1.32 × 1.24 × 1.35 cm. The anatomy-pathological result showed pancreatic neuroendocrine tumor WHO Grade II, functional, consistent, and clinically to insulinoma on the tail of the pancreas. The patient was treated with hydrocortisone, nifedipine, and octreotide. The patient underwent laparotomy partial pancreatectomy. In post-surgery condition, she had good drink tolerance, no episode of recurrent seizure, and blood glucose was controlled. CONCLUSION: Insulinoma is a rare disease. The diagnosis was challenging. This case report presents the diagnostic work-up and management of a patient with a persistent hypoglycemia condition that was diagnosed as insulinoma.